2009
DOI: 10.1182/blood-2009-07-143545
|View full text |Cite
|
Sign up to set email alerts
|

How I treat EBV lymphoproliferation

Abstract: Epstein-Barr virus (EBV)- IntroductionEpstein-Barr virus (EBV) lymphoproliferative disease (LPD) is the result of the outgrowth of EBV-infected B cells that would normally be controlled by an effective EBV-specific cytotoxic T-cell response. LPD may occur during both primary and secondary immune deficiencies and even in some persons without documented immunodeficiency. In this article, I focus on EBV type III latency B-cell lymphoproliferation, which occurs during the immunosuppression that follows hematopoiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
253
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(263 citation statements)
references
References 68 publications
1
253
1
2
Order By: Relevance
“…20 LPD after HSCT typically occurs within the first 6 months post transplant, before reconstitution of the EBV-specific cytotoxic T-cell response. 7 In the first patient, EBV-LPD occurred late after UCBT (at 9 months post UCBT), highlighting the concern of a relatively slow immune reconstitution after UCBT. 21,22 However, immunosuppressive treatment at the time of the occurrence of EBV-LPD could have altered the specific immune recovery, as previously reported for CMV in the same setting.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…20 LPD after HSCT typically occurs within the first 6 months post transplant, before reconstitution of the EBV-specific cytotoxic T-cell response. 7 In the first patient, EBV-LPD occurred late after UCBT (at 9 months post UCBT), highlighting the concern of a relatively slow immune reconstitution after UCBT. 21,22 However, immunosuppressive treatment at the time of the occurrence of EBV-LPD could have altered the specific immune recovery, as previously reported for CMV in the same setting.…”
Section: Discussionmentioning
confidence: 92%
“…7,28 In addition, an ever growing number of studies suggested that preemptive therapy with rituximab may be highly effective in controlling viral proliferation and avoiding progression into EBV-related LPD. 29,30 Of note, the efficacy of rituximab was mainly observed in the preemptive setting, but to a lesser extent once EBV-related LPD was fully established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As most cases of PTLD arise among donor-or recipient-derived B-cells, one strategy to prevent the development of PTLD is to eliminate EBVinfected B-cells in the early phase after HSCT. Monitoring the EBV-DNA load in the peripheral blood in addition to administering preemptive rituximab therapy has recently been reported to be a successful approach to preventing the development of B-cell PTLD (1,2). EBV-specific tetramer analyses using flow cytometry can also be useful for detecting EBV-specific cytotoxic T-cells (CTL), the actions of which are negatively associated with the development of PTLD (3).…”
Section: Introductionmentioning
confidence: 99%